Ethnomycological knowledge among Kaqchikel, indigenous Maya people of Guatemalan Highlands - J. P. Mérida Ponce; M. A. Hernández Calderón; O. Comandini; A. C. Rinaldi; R. Flores Arzú (BMC, 2019)
Abstract Background The Guatemalan Highlands is a region of great but so far poorly known mycological diversity. People living in this area have long used wild fungi as a source of food and income. However, our knowledge of the ethnomycological practices of the Mayan peoples of Guatemala is still rudimental, especially if compared with information reported for the neighboring region of Mexico. Among the main indigenous groups of the Maya people inhabiting the highlands of Central Guatemala, stand the Kaqchikel, accounting for nearly 8% of the entire Guatemalan population. The main aim of this study was to record the traditional knowledge and use of edible wild mushrooms by inhabitants of the municipality of San Juan Sacatepéquez that lies at the heart of the Kaqchikel area in the central highlands of Guatemala, also describing the relevant selling practices and dynamics. A secondary aim was to compare the diversity and composition of the mushroom assemblage offered at the market with the macrofungal diversity of woods in the area. Methodology This study is the result of 4 years of ethnomycological research, conducted through continuous visits to the municipal market and focused interviews with collectors and vendors. Field sampling in pine-oak forested areas surrounding San Juan Sacatepéquez, from where the mushrooms sold at the market are foraged, were also conducted, in the presence of local collectors. Results The results show a significant richness of species sold in the market, a network of commerce of purchase, sale, and resale of several species, with relatively stable prices, and knowledge about edible and inedible species that is transmitted mainly within the family nucleus. The business of selling mushrooms in the market is an exclusive activity of women, who are supplied by collectors or by other vendors. Fungi are sold and bought only as food, while no consumption of hallucinogenic mushrooms or medicinal mushrooms was recorded. Several species of Amanita, Cantharellus, Boletus, Lactarius, and Russula were those most commercialized in the 4 years of the study, but we also spotted fungi never reported before as consumed in the country, including Gastropila aff. fumosa (= Calvatia fumosa) and several species of Cortinarius. Field sampling in nearby pine-oak forests confirmed an elevated local macrofungal diversity. Conclusion Our study unveiled the contemporary wealth of Kaqchikel culture for what concerns mushrooms, demonstrating that mushrooms continue to be culturally and economically important for these communities despite the erosion of traditional knowledge. Our results also confirmed the need to investigate in greater detail the Guatemalan mycodiversity that is vast and poorly known.